Treatment of pelvic lymphocoele: a case report and review of the literature - Rechberger, Tomasz; Wróbel, Andrzej; Tomaszewski, Jacek; Postawski, Krzysztof (Menopause Review/Przegląd Menopauzalny, 2010)
Pelvic lymphocoele is a result of systemic surgical lymph nodes removal leading to the accumulation of proteinrich interstitial fluid in the extraperitoneal space. The presence of fluid arrested within the tissue accompanied by a decrease in the amount of oxygen and proteolytic activity evoke chronic infection. The excess of protein in the presence of a bacterial infection additionally deteriorate lymphatic dysfunction. The most common bacteria causing the infection are haemolytic streptococci. Moreover, the oedema makes tissue nutrition and healing of the wound difficult. There are no randomised clinical trials devoted to specific lymphocoele treatment. The aim of the therapy is stabilization of lymphocyst, its decrease by needle aspiration and the improvement of the patient’s quality of life as well as the prevention and treatment of side effects. In the article we describe both surgical and pharmacological options of lymphocoele treatment with special attention paid to sclerotherapy.